Evaluasi pemberian ekstrak daun Pluchea indica less pada pakan terhadap pertumbuhan benih ikan Patin (Pangasius hypopthalamus). - Sri Herlina; Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
The purpose of this study was to evaluate the effect of the addition of Pluchea indica less leaves extracts to the optimal feed and dosage in commercial feed on growth and survival rate (survival) of catfish seedlings. The study used a completely randomized design (CRD) with 3 (three) treatments, namely treatment P1 Feeding with the addition of leaf extracts of Pluchea indica less as much as 5 ml / kg of feed, P2 treatment 10 ml / kg of feed and P3 treatment of 15 ml / kg of feed. The parameters observed were relative weight growth, survival rates (survival). The results showed that the administration of Pluchea indica less leaves to the feed had a significant effect on the growth of Catfish (Pangasius hypopthalamus) seeds where the highest treatment was in the P3 (15 ml / kg of feed) treatment of 100.13% followed by P2 (10 ml / kg of feed treatment) ) amounting to (80.35%) and treatment P1 (5 ml / kg of feed) amounting to (58.12%). Keywords : Pluchea indica less, growth, Pangasius hypopthalamus